Bite raising appliance for treatment of temporomandibular joints (TMJ) myofascial pain dysfunction syndrome and internal derangement - Najat R. Ali; Susan N. Abdulakdir (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Tempromandibular joint disorder is common disorder that has multifactorial etiology presented with cardinal clinical presentation of pain, joint sound and limitation of mouth opening. The most common causes of this disorder are muscular which are commonly referred as a myofascial pain and dysfunction other cause include internal derangement of TMJ structures.Objectives: This study was established to determine the effect of bite raising appliance in the treatment of myofacial pain and internal derangement of temporo-mandibular joint.Material & methods: This is a prospective study for 100 cases of temporo-mandibular joint disorder (TMD) patients were selected from department of maxillofacial surgery in Azadi Teaching Hospital, Kirkuk, Iraq and from the private clinic in the period of Jan-2012 to Dec. 2020.Results & conclusion: After 3 months of clinical follow-up the results revealed that bite raising appliance has a good outcomes in relieving pain, clicking and increase mouth opening in patient with myofacial pain and internal derangement of TMJ.